Improving the knowledge base of Vulnerable Marine Ecosystems’ distribution in the Amendolara Bank (Ionian Sea) - PALUMMO, VALERIA; MILISENDA, GIACOMO; PICA, DANIELA; CANESE, SIMONEPIETRO; SALVATI, EVA; SPANÒ, NUNZIACARLA; ROMEO, TERESA; GRECO, SILVESTRO (Mediterranean Marine Science, 2024)
The Amendolara Bank was recently designated as a Site of Community Importance; however, information on its ecosystems remains limited, with a particular dearth of knowledge regarding the deeper zone (>100 m). Previous studies have discovered the existence of Vulnerable Marine Ecosystems (VMEs) within the bank, underscoring the necessity for more comprehensive data and its significance in terms of conservation in the Ionian Sea. This study aims to investigate various aspects of the bank using Remotely Operated Vehicles (ROVs) to shed light on the possible presence of VME indicator species, their relationship with environmental variables, their connection with the observed fish, and to assess anthropogenic impact via the identification of fishing gear within the study area. This present research provides new information on the biodiversity of the Amendolara Bank, revealing the presence of four VME indicator species including the first sightings of black coral Antipathella subpinnata and the precious red coral Corallium rubrum. Moreover, it provides evidence on the interaction between fish fauna and VME indicator species as well as signs of anthropogenic impact from abandoned, lost, or otherwise discarded fishing gear (ALDFG). These findings highlight the urgent need for additional research to improve the knowledge base on the biodiversity of this unique spot in the Ionian Sea which would in turn ensure the development and implementation of more effective conservation and management measures.